2015
DOI: 10.7314/apjcp.2015.16.2.689
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of EGFR Mutations in Non-small Cell Lung Cancer Patients: Screening Data from West Siberia

Abstract: Background: Incorporation of molecular analysis of the epidermal growth factor receptor (EGFR) gene into routine clinical practice has shown great promise to provide personalized therapy of the non-small cell lung cancer (NSCLC) in the developed world. However, the genetic testing of EGFR mutations has not yet become routine clinical practice in territories remote from the central regions of Russia. Therefore, we aimed to study the frequency of major types of activating mutations of the EGFR gene in NSCLC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Han et al reported 9.9% and 3.7% EGFR mutation in SCC and 49.3% and 18% mutation in adenocarcinoma from Asia-Pacific region and Russia respectively [3]. EGFR mutation in SCC varies between 0-25% in different regions of the world [6, 29, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al reported 9.9% and 3.7% EGFR mutation in SCC and 49.3% and 18% mutation in adenocarcinoma from Asia-Pacific region and Russia respectively [3]. EGFR mutation in SCC varies between 0-25% in different regions of the world [6, 29, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Начало лечения на ранних стадиях позволяет существенно увеличить шансы пациента на выздоровление и быстрейшую социальную и трудовую адаптацию. При этом пятилетняя выживаемость после лечения I стадии составляет 70 %, а IV стадии -менее 5 % [3,4].…”
Section: Introductionunclassified
“…Other than genetic factors, patient characteristics including gender, race and lifestyle influence the effectiveness of the treatment for NSCLC ( 5 ). The most prominent genetic factor associated with the responsiveness to NSCLC treatment is a mutation in EGFR ( 6 , 7 ). Mutations in EGFR mediate the carcinogenic effect by manipulating the apoptotic mechanism ( 8 ).…”
Section: Introductionmentioning
confidence: 99%